Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) di PT. X: PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) DI PT. X - Efendi, Falin Rizal; Sulastri (Fakultas Teknik Universitas Hamzanwadi, 2025)
Hazardous and toxic waste (HTW) is waste containing hazardous substances that have the potential to pollute the environment and endanger human health if not managed properly. Tapioca flour processing company PT. X produces HTW from operational activities in the workshop area. This study aims to examine the practice of HTW management in the company with a focus on compliance with regulations and the effectiveness of the management strategies implemented. The results of the study indicate that there are eight types of HTW produced, namely used cloth (B110d), used oil (B105d), used packaging (B104d), oil filters (B109d), TL lamps and cartridges (B107d), used batteries (A102d), fly ash (B409), and bottom ash (B410). In general, B3 waste management has been implemented well through reduction procedures, packaging and labeling, storage at Temporary Storage Sites (TSS), and transportation by licensed third parties. However, several aspects still require improvement, particularly regarding emergency response facilities at the HTW TSS which are not yet fully available, so improvements are needed for safety and to ensure preparedness in facing potential emergencies.